1998
DOI: 10.1136/bmj.316.7142.1430
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention in coronary heart disease: baseline survey of provision in general practice

Abstract: Objective: To determine secondary preventive treatment and habits among patients with coronary heart disease in general practice. Design: Process of care data on a random sample of patients were collected from medical records. Health and lifestyle data were collected by postal questionnaire (response rate 71%). Setting: Stratified, random sample of general practices in Grampian.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
132
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(147 citation statements)
references
References 19 publications
(25 reference statements)
12
132
1
2
Order By: Relevance
“…The same was applied to practice characteristics that had a significant relation either with the 1 The Minimal Intervention Strategy is a smoking cessation package shown to be feasible and effective. 2 Checked by observation whether the leaflets were within reach during the consultation. 3 Adequate ancillary staff present =0.8 full-time equivalent practice assistance per 2500 patients (norm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same was applied to practice characteristics that had a significant relation either with the 1 The Minimal Intervention Strategy is a smoking cessation package shown to be feasible and effective. 2 Checked by observation whether the leaflets were within reach during the consultation. 3 Adequate ancillary staff present =0.8 full-time equivalent practice assistance per 2500 patients (norm).…”
Section: Discussionmentioning
confidence: 99%
“…1 100% computerized =practices that do not use any written medical records: all patient data were entered into the computer. 2 Systematic entries were at least necessary for hypertension, diabetes mellitus, individual and family cardiovascular history. 3 The risk factors that had to be recorded separately were hypertension, smoking and individual cardiovascular history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in spite of the ample evidence for recommending aspirin usage for secondary prevention of cardiovascular disease 6 , recent studies in USA and Europe revealed significant gaps in secondary prevention 7,8 with suboptimal prescription rates in patients who already have coronary heart disease [9][10][11][12] .…”
mentioning
confidence: 99%
“…Several papers have reported concern about the small use of these drugs and the resulting damage suffered by patients who do not receive this treatment [9][10][11] , even in the USA and in Europe. In Great Britain, a recent study showed that only in 17% of patients with indication of secondary prevention presented lipid concentrations, according to the official guidelines 11 . In our environment, the situation is more critical yet, because the socioeconomic situation in Brazil prevents the correct use of statins, even when the cardiologists are absolutely sure about its indication.…”
mentioning
confidence: 99%